### Discussion :: General Principles - General Questions (Q.No.1)

Naveen said: (Dec 10, 2010) | |

x^2-16=0 (x-4)*(x+4)=0 (x-4)=0 or (x+4)=0 x=4 , -4 |

Billa said: (Jan 28, 2011) | |

x^2 - 16 = 0 x^2 = 16 x = sqrt(16) x = 4 or -4 |

Prabu said: (Feb 25, 2011) | |

Well Naveen you gave the exact method to find the ans. |

Nishita said: (Apr 28, 2011) | |

(x^2-16)=0 (x^2-4^2)=0 (x-4)(x+4)=0 therefore, (x-4)=0,x=4 (x+4)=0,x=-4 hence,x=4,-4 |

Lakshmi said: (Jun 3, 2011) | |

x^2 = 16 x = sqrt(16) Therefore, x = +4 or -4. |

Balajikumar said: (Jun 23, 2011) | |

LAKSHMI Method is best one |

Sri said: (Jul 8, 2011) | |

Well billa's method is also good. |

Kamal said: (Jul 16, 2011) | |

Naveen is absolutely correct!! |

Damodaran said: (Aug 13, 2011) | |

Well the three methods are good. |

Ashok said: (Aug 22, 2011) | |

x^2-16=0 x^2=16 x=sq.root 16 i.e.x=+ or - 4 x=4;x=-4 |

Adil said: (Sep 5, 2011) | |

(x)2-(4)2=0 (x-4)(x+4)=0 x-4=0,x+4=0 x=4,x=-4 |

Adil said: (Sep 5, 2011) | |

Lakshmi I like your answer. |

James said: (Sep 26, 2011) | |

Laxmi's method is good. |

Manik said: (Nov 2, 2011) | |

Answer is correct. |

Ashok.L.B.Naik said: (Feb 8, 2012) | |

@Naveen's method is easy to solve. |

Santhosh said: (Feb 24, 2012) | |

Billa's method is easiest and understandable. |

Pravi said: (Mar 8, 2012) | |

Laxi method is easy. |

Raja said: (May 23, 2012) | |

Billa's method is very easy. |

Murali said: (Jun 28, 2012) | |

X^2-16=0. X=sqrt (16). X=4, -4. |

Kamal said: (Sep 16, 2012) | |

Why do use iota. Ioti (i) its value is also -1. That answer is also right option b. |

Cherry said: (Sep 25, 2012) | |

x^2 - 16 = 0 x^2 = 16 x = sqrt(16) x = 4 or -4 |

Rakesh said: (Jan 31, 2015) | |

(x)2-16 = 0. We know that a2-b2 = (a+b)(a-b). (x)2-(4)2 = 0. (x+4)(x-4) = 0. x = -4, +4. |

Rupa said: (Jan 27, 2016) | |

X^2 - 16 = 0. X^2 = 16. X = 4, -4. |

Arun said: (Jul 22, 2016) | |

Your method is easy to solve. @Naveen. |

Winfred said: (Nov 13, 2016) | |

@All, Nice solution thanks for it. |

Darshan Dodia said: (Jul 5, 2017) | |

According to Quadratic Equation ax^2+bx+c=0, roots of equation x = (-b+/-sqrt(b^2-4ac))/(2a). |

Ajmal K said: (Nov 12, 2018) | |

X^2-16=0. X= +/-(√16), X= +/-(4), X=(+4) & x=(-4). |

#### Post your comments here:

Name *:

Email : (optional)

» Your comments will be displayed only after manual approval.